2008
DOI: 10.3390/molecules13010003
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectra of Sparteine N1-oxide and α-Isosparteine N-oxide

Abstract: Sparteine N1-oxide and α-isosparteine N-oxide were prepared and their structures determined for the first time by 1H- and 13C-NMR spectroscopy using two-dimensional techniques. The N-oxide effects were also calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In the literature, there are several examples of the combination of experimental NMR data with calculated NMR parameters (shielding nuclear constants and scalar couplings) addressing various stereochemical problems, e.g. the conformation of sparteine N ‐oxides,14, 15 the conformation and configuration of tertiary amines via GIAO‐derived 13 C chemical shifts and a multiple independent variable regression analysis,16 the conformation of N ‐substituted piperidines and pyrrolidines17 or the relevance of the calculated 1 H, 13 C and 15 N shieldings in amines in conformational analysis 18. GIAO NMR calculations combined with probability analysis were also used for the assignment of stereochemistry when the NMR data were available only for one diastereoisomer 19…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are several examples of the combination of experimental NMR data with calculated NMR parameters (shielding nuclear constants and scalar couplings) addressing various stereochemical problems, e.g. the conformation of sparteine N ‐oxides,14, 15 the conformation and configuration of tertiary amines via GIAO‐derived 13 C chemical shifts and a multiple independent variable regression analysis,16 the conformation of N ‐substituted piperidines and pyrrolidines17 or the relevance of the calculated 1 H, 13 C and 15 N shieldings in amines in conformational analysis 18. GIAO NMR calculations combined with probability analysis were also used for the assignment of stereochemistry when the NMR data were available only for one diastereoisomer 19…”
Section: Introductionmentioning
confidence: 99%
“…Thermseedline M (13) had a molecular formula of C 15 H 20 N 2 O 4 as determined by its HRESIMS (m/z: 261.1590 [M + H] + ; calcd for 261.1598). The NMR data showed that 13 was a hydroxyl analog of thermopsine (25). The 1 H-1 H COSY correlations of H 2 -13/H-14/H 2 -15 demonstrated that the hydroxyl group was connected to C-14 (δ C 64.4) (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The NMR spectroscopic data of 11 showed signals for five methylenes, eight methines, and three quaternary carbons. The aforementioned data suggested that 11 was a homolog of thermopsine (25). 20 The downfield shifts of C-12 (δ C 54.9, 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations